Financial Analysis Of KM Tresna's Purse Seiner Operating In The South Of Java Indonesian Ocean - Haris, Dendi; Sutono HS, Dian; Narayana, Gelar Fatria; Istrianto, Kadi; Sadir, Edizul Adiwijaya; Suratna, Suratna (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2023)
Purse seine is an active type of fishing gear because in fishing operations the vessel circles the net around the target by circling the net around a school of fish then the bottom of the net is pursed by pulling the crimped rope. The operation of the purse seine fishing gear is by circling a school of fish around FADs by utilizing the habit of positive taxis photo fish. The stages of operating the purse seine are the preparation stage, the stage of lowering the fishing gear (setting), the stage of withdrawing the wrinkled line (purshing) then the stage of withdrawing the fishing gear (hauling). For financial analysis using 4 indicators in determining the feasibility of a business carried out at KM Tresna including Profit and Loss, R/C Ratio (IRR), Payback Period (PP) and ROI (Return Of Investment). Business feasibility at KM Tresna taking into account profits, R /C Ratio, Payback Period and Return on Investment. Where is the result of calculations in 1 year Tresna KM gets a net profit of Rp. 526,300,717, the R/C is 1.25, which means that the business is very feasible and can be developed. Investment costs can be returned for 3.72 years in the calculation of the payback period and the ROI calculation reaches 26,85%. From all these calculations it can be concluded that the effort on KM Tresna can be said to be feasible.